Retrospective Analysis of Reasons for Discarding Whole Blood and Blood Components at Tertiary Care Hospital Blood Bank in South Gujarat - Roy, Niketa; Shah, Ankita (National Journal of Community Medicine, 2017)
Introduction: Blood transfusion is an integral part of medical practice. Proper utilization of blood and its components with minimal wastage is necessary because each unit of blood is precious. In this study, the aim was to find out the main causes for discarding whole blood and components so that the wastage can be minimized and sufficient amount of safe blood can be supplied. Materials and Methods: A retrospective study was carried out during January 2015 to December 2015 at tertiary care hospital blood bank in Surat, Gujarat. Results: Of the 19338 blood components prepared, 2256 (11.6%) were discarded. The main reason for discarding blood and blood components were expiry of Platelet concentrate (27.4%) followed by Fresh Frozen Plasma due to leakage (25.7%) and lipemic (11.4%) cause, suboptimal collection of blood units(16.1%), and seroreactivity (5.8%) for various transfusion transmitted infections. Discard rate for whole blood and red cell concentrate was 557 (4.85%). Conclusion: A properly conducted donor screening, notification and counseling of permanently deferred donors will reduce seroreactive blood units with properly implemented blood transfusion policies and proper training of staff will help in reducing the causes of discard.